ACE2 and TMPRSS2 genetic polymorphisms as potential predictors of COVID−19 severity and outcome in females - Sanja Matic; Dragan Milovanovic; Dragan Milovanovic; Zeljko Mijailovic; Zeljko Mijailovic; Predrag Djurdjevic; Predrag Djurdjevic; Srdjan Stefanovic; Danijela Todorovic; Katarina Vitosevic; Katarina Vitosevic; Vanja Canovic; et al. (Frontiers in Medicine)
IntroductionACE2 and TMPRSS2 represent the major gateways for SARS-CoV-2 cell entry. The presence of functional ACE2 and TMPRSS2 genetic polymorphisms that affect gene expression may affect the risk of severe form of COVID-19 and its fatal outcome.Material and patientsThis observational study enrolled 178 hospitalized patients diagnosed with SARS-CoV-2 infection at the University Clinical Centre of Kragujevac, Serbia. Demographic, clinical, and laboratory data were gathered at admission. Genotyping for single nucleotide polymorphisms of ACE2 (rs2106809 and rs2074192) and TMPRSS2 (rs2070788 and rs4818239) was performed using the Real-Time PCR method with TaqMan assays.ResultsControlling for other factors of influence, such as CCI, N/L ratio, LDH level, and pO2, we showed that females with TMPRSS2 rs2070788 A/A genotype were less likely to develop severe COVID-19 (odds ratio [OR] [95% confidence interval (95% CI)]: 0.030 [0.001; 0.862]). Additionally, the likelihood of dying of SARS-CoV-2 infection was lower in female carriers of at least one ACE2 rs2106809 C allele (OR [95% CI]: 0.004 [0.000; 0.981]).ConclusionOur findings indicate TMPRSS2 rs2070788 and ACE2 rs2106809 polymorphisms as independent predictors of severity and outcome of COVID-19 in females.